(untitled) (Indian Journal of Chemistry (IJC), 2026)
Kinetic studies of hydrolysis of the two isochemical azomethine sites present in 1,2-bis(salicylidinimino)ethelene (1) abbreviated as EDA -Sal and one of its novel mononuclear copper (II) complex abbreviated as Cu(EDA - Sal) (2) have been studied in the varied pH range 1-12, and at different temperatures. The investigations indicate that based on pH, the aliquot (1) exists in several acid - base forms. The acid-base equilibrium and resonace effects have been found to be responsible for near simultaneous hydrlysis of azomethine sites present in the molecules.The repetitive spectral profiles of both the selected compunds reveal that the kinetic mixture exhibit isosbestic points in entire pH range of study, indicating the involvement of only two absorbing species throughout the reaction path. The hydrolysis follows pseudo - first order kinetics in both schiff base and its corresponding complex. Intersetingly, except in acidic range, the complex is found to be stable. the difference in rate of hydrolysis of (2) from that of (1) and the possible influencing factors are discussed. By Arrhenius and Eyring methods activation energy Ea and other thermodynamic parametres such as DH#, DG# and DS# are evaluted. Keywords: EDA -Sal; Cu(EDA – Sal); hydrolysis; isosbesticity, Thermodynamic Parameters